Tidal Energy: Perspective of Bangladesh (Journal of Bangladesh Academy of Sciences, 2018)
Bangladesh is blessed by the nature with renewable resources that are used all over the world in a wide range but in our country it is limited. The country has vast ocean area with various power resources such as Wave energy, Ocean Thermal Energy Conversion (OTEC) and Tidal energy. In the Bay of Bengal, the tidal range and tidal stream speed indicate the potentiality of tidal power generation in Bangladesh. This paper describes various methods of utilizing tidal power to generate electricity and assess the tidal energy resources of three potential sites of Bangladesh. The tidal data recorded by the Department of Hydrography of The Chittagong Port Authority (CPA) and Bangladesh Inland Water Transport Authority (BIWTA) have been analyzed. This study clearly indicates the bright prospects of tidal power in Bangladesh.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 201-215, 2017